Влијанието на инструментите на централната банка врз финансиската стабилност - Мучева Михајловска, Елена (Економски факултет, УКИМ, Скопје, 2016)
The dissertation uses seven modified methods, and introduces a new method for creating single indicator - an index of financial stability and monetary index of the case of Republic of Macedonia. One of the contributions of this paper is the method - average index (average of multiple indexes created with multiple methods), which proved to be more reliable than using individual indexes reflection of the state of a system. Also, the dissertation published other new modified methods of creating indexes including: portfolio modified method of variance decomposition, modified portfolio method with dynamic variances, method of VaR- Value at risk and modified portfolio method of signals. The idea of introducing this type of indicators, is analyzing the relationship between financial stabili ty and monetary policy in the country. The financial stabili ty index has shown that in times of global financial crisis, in the case of Macedonian economy, the most important drivers are credit and deposit activity of banks, with some influence by stock index and the housing price index. Increased financial stress is triggering the materialisation of credit risk, which effects are usually felt minimum after a period of two quarters. Tested structural VAR model showed that there is a strong and instant mutual relationship between financial stabili ty index and monetary policy. TVAR model showed that the reaction of financial stabili ty index to the change in monetary measures depends on the state in which the financial system (state of stabili ty / state of stress), and that in times of financial stress, restrictive monetary measures add to downward movement of financial stability index. TVAR and linear VAR models which incorporated financial stability index have greater predictive power than linear VAR models excluding financial stability index.
Тhe effects of the Central Bank instruments on Financial Stability
Докторска дисертација одбранета во 2016 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: financial stability indices, financial crisis, monetary instruments